Photoregulation of the Carotenoid Biosynthetic Pathway in Albino and White Collar Mutants of Neurospora crassa - Harding, Roy W. (1981)
The conversion of isopentenyl pyrophosphate to phytoene in Neurospora crassa requires both a soluble and a particulate fraction. Soluble and particulate enzyme fractions obtained from light-treated and dark-grown wild type, albino-1, albino-2, albino-3, and white collar-1 strains were mixed in various combinations, and the activity for conversion of [1-(14)C]isopentenyl pyrophosphate to phytoene was assayed. From such experiments it can be concluded that: (a) albino-3 is defective in the soluble fraction; (b) albino-2 is defective in the particulate fraction; (c) the in vivo light treatment increases the enzyme activity in the particulate fraction; (d) this light effect occurs in wild type, albino-1, and albino-3 strains; and (e) enzyme activity is present in the particulate fraction obtained from the white collar-1 mutant, but the in vivo light treatment does not cause an increase in this activity. To measure directly the level of particulate enzyme activity, [(14)C]geranylgeranyl pyrophosphate was used as a substrate. This compound, which is not available commercially, was synthesized enzymically using extracts of pea cotyledons. Particulate enzyme fractions obtained from wild type, albino-1, and albino-3 strains incorporate [(14)C]geranylgeranyl pyrophosphate into phytoene, and this activity is higher in extracts obtained from light-treated cultures. The particulate fraction obtained from the white collar-1 mutant also incorporates [(14)C]geranylgeranyl pyrophosphate into phytoene, but the in vivo light treatment does not cause an increase in this activity. No incorporation occurs when particulate fractions obtained from either dark-grown or light-treated albino-2 cultures are assayed. The soluble enzyme fraction obtained from the albino-3 mutant was shown to be almost totally defective in enzyme activity required for the biosynthesis of [(14)C]geranylgeranyl pyrophosphate from [1-(14)C]isopentenyl pyrophosphate. An in vivo light treatment increases the level of this activity in wild type, albino-1, albino-2, and albino-3 strains, but not in the white collar-1 mutant. A model is presented to account for all of the results obtained in this investigation. It is proposed that the white collar-1 strain is a regulatory mutant blocked in the light induction process, whereas the albino-1, albino-2, and albino-3 strains are each defective for a different enzyme in the carotenoid biosynthetic pathway.